2008
DOI: 10.1111/j.1365-2133.2008.08629.x
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of IgA anti-epidermal transglutaminase antibodies in dermatitis herpetiformis

Abstract: IgA antibodies to TG3 are elevated in patients with DH and adults with CD. The progressive expansion of the epitope-binding profile of IgA antitransglutaminase antibodies in patients with CD may explain the development of DH in patients with undiagnosed CD during their adult life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
62
0
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(72 citation statements)
references
References 18 publications
6
62
0
4
Order By: Relevance
“…Eleven DH cases had the level of serum IgA antibodies to TG3 above the manufacturer's cut-off value (52.4%); range of levels was 4.79-176.52 AU/ml. The low percentage of DH cases with elevated levels of serum IgA antibodies to TG3 in this study should not be considered unusual since in a recently published investigation only 52% of DH patients were shown to have those levels elevated [12]. It is known that dapsone impairs the functions of neutrophils, but our results were not influenced by this drug as none of patients was treated with dapsone prior to the establishment of the diagnosis of DH.…”
mentioning
confidence: 32%
“…Eleven DH cases had the level of serum IgA antibodies to TG3 above the manufacturer's cut-off value (52.4%); range of levels was 4.79-176.52 AU/ml. The low percentage of DH cases with elevated levels of serum IgA antibodies to TG3 in this study should not be considered unusual since in a recently published investigation only 52% of DH patients were shown to have those levels elevated [12]. It is known that dapsone impairs the functions of neutrophils, but our results were not influenced by this drug as none of patients was treated with dapsone prior to the establishment of the diagnosis of DH.…”
mentioning
confidence: 32%
“…It frequently is manifest in childhood, although it can first become symptomatic at any time in life. IgA Abs to TG2 have become the serologic hallmark and a diagnostic criterion for celiac disease and develop early in the course (23). They are thought to develop from an immune response to TG2, which plays an essential role in metabolizing the gliadin Ag.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies showed that the ETG, rather than the TTG is the dominant autoantigen in DH [12,13]. This difference in autoantigens may be the reason for the different clinical presentation seen in DH and CD, which are thought to share same pathogenetic background.…”
Section: Discussionmentioning
confidence: 93%